2017
DOI: 10.21091/mppa.2017.2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Specific Strength Training vs General Fitness Training on Professional Symphony Orchestra Musicians: A Feasibility Study

Abstract: Musculoskeletal symptoms, especially in the upper body, are frequent among professional symphony orchestra musicians. Physical exercise may relieve pain but might also interfere with playing performance. OBJECTIVE: To evaluate the feasibility and effect of “specific strength training” (SST) versus “general fitness training” (GFT). METHODS: A feasibility study using randomized controlled methods. Primarily, evaluations involved self-reported impact on instrument playing and satisfaction with the interventions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
16
0
4
Order By: Relevance
“…No statistically significant changes in MCD were found in violinists after scapula taping, in musicians participating in yoga lifestyle interventions, or in orchestra musicians attending music didactic lectures and receiving instructions for home exercises or trigger point treatment with radial shockwave therapy combined with physical therapy or specific strength training in comparison to a control group (Ackermann et al 2002a;Khalsa and Cope 2006;Khalsa et al 2009;Brandfonbrener 1997;Damian and Zalpour 2011;Nygaard Andersen et al 2017). However, two studies reported significant improvements within the treatment groups but not in the control group (Damian and Zalpour 2011;Nygaard Andersen et al 2017). Tuina application and groningen exercise therapy did produce statistically significant reductions in pain in the treatment groups compared to the control groups (de Greef et al 2003;Sousa et al 2015a, b).…”
Section: Used Outcome Parameters Of Interventional Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…No statistically significant changes in MCD were found in violinists after scapula taping, in musicians participating in yoga lifestyle interventions, or in orchestra musicians attending music didactic lectures and receiving instructions for home exercises or trigger point treatment with radial shockwave therapy combined with physical therapy or specific strength training in comparison to a control group (Ackermann et al 2002a;Khalsa and Cope 2006;Khalsa et al 2009;Brandfonbrener 1997;Damian and Zalpour 2011;Nygaard Andersen et al 2017). However, two studies reported significant improvements within the treatment groups but not in the control group (Damian and Zalpour 2011;Nygaard Andersen et al 2017). Tuina application and groningen exercise therapy did produce statistically significant reductions in pain in the treatment groups compared to the control groups (de Greef et al 2003;Sousa et al 2015a, b).…”
Section: Used Outcome Parameters Of Interventional Studiesmentioning
confidence: 95%
“…Five studies explicitly included participants with complaints to investigate the effectiveness of the interventions (Sousa et al 2015a, b;Damian and Zalpour 2011;de Greef et al 2003;Steinmetz et al 2009). Six studies included both musicians with complaints and musicians without complaints and investigated the prevalence and intensity of complaints before and after the interventions (Nygaard Andersen et al 2017;Ackermann et al 2002b;Brandfonbrener 1997;Chan et al 2014;Khalsa and Cope 2006;Khalsa et al 2009) or during the interventions compared to control conditions (Ackermann et al 2002b).…”
Section: Study Population Of Interventional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another source of data pertaining to musicians' physical fitness can be found in studies examining the impact of physical activity and exercise on reactivity to psychosocial stress (Wasley et al, 2012) or for rehabilitation purposes (Chan et al, 2000(Chan et al, , 2013b(Chan et al, , 2014Ackermann et al, 2002;Kava et al, 2010;Andersen et al, 2017). For example, in a study examining the impact of an exercise program on stress reactivity with 46 conservatoire music students (mean age = 21 years), Wasley et al (2012) reported healthy body mass index (BMI) and average aerobic fitness (VO 2max ) and found that fitter individuals experienced lower anxiety after performing.…”
Section: Introductionmentioning
confidence: 99%
“…The most consistent finding was the decrease in neck/shoulder pain among office workers (2,3,5,7,12,2224,32,64), dentists (29), musicians (10), and industrial technicians [(40,41) (95)]. This effect was present with both strength and aerobic training and was not dependent on how the 1 hr of exercise training was distributed over the work days (22).…”
Section: Pa As Cure For Muscular Pain and Health Enhancementmentioning
confidence: 85%